RELIABILITY AND VALIDITY STUDIES OF THE GENDER EQUITABLE MEN SCALE IN TURKISH MEN - Gülten UÇAN (Fırat University, 2019)
In order to provide an egalitarian approach to men’s gender attitude which have negative impacts both on women’s and on their own lives, various international programs are carried out. In order to assess the efficacy of these programs and to demonstrate changes brought about by these programs, various measurement tools have been developed. The present study aims to adapt the Gender Equitable Men's Scale (GEMS) into Turkish and to determine its psychometric properties. The study designed as a cross-sectional one is a methodological survey study. The Cronbach's alpha coefficient of the scale is 0.856. The Root Mean Square Error of Approximation (RMSEA) and Comparative Fit Index (CFI) values of the subscales of the GEMS ranged from 0.018 to 0.076 and from 0.969 to 0.996 respectively. The GEMS adapted to Turkish society is a valid and reliable scale.